Modeling of professionally oriented tasks by means of innovative forms of future music art teacher training - Bezemchuk, Larisa; Fomin, Volodymyr (Professional Art Education, 2021)
The purpose of the article is to determine the specifics of the professional training of the future music teacher in the conditions of the organization of distance education, where interactive forms and methods are given a significant importance.Methods & methodology. The research is based on the leading positions of scientists regarding the development of art education in today’s conditions – axiological, systemic, personal-activity and cultural based on the principle of integrity, mutual coherence, considering the integrative approach in the organization of the educational process.The scientific novelty of the article lies in the definition of interactive forms and methods of distance education, considering the specifics of training future music teachers for professional activity through the introduction of educational electronic courses, multimedia software and methodological support, the use of audio-video materials, television educational programs, etc.Results. The theoretical and practical aspects of the professional training of future music teachers in the conditions of distance learning on the Moodle platform are revealed. It has been proven that the specifics of the professional training of future music teachers in the process of organizing distance learning requires new development of program-pedagogical systems and software tools. Certain pedagogical conditions have been defined, including: the presence of clear goal-setting for teachers and students; computerization of the educational process in professional musical disciplines; mastering the technologies and means of distance learning, taking into account the specifics of music education; focusing on the selection of the content of educational and methodical material for distance learning and the creation of a favorable informational and methodical environment; the application of distance learning network technologies as an environment for the interaction of subjects of musical-pedagogical interaction. The advantages and disadvantages of organizing the educational process of future music teachers in the conditions of distance learning are presented. Recommendations regarding the use of effective technologies for the organization of distance education of future music teachers are provided.
Keywords: education; professional training; distance learning; teacher; musical art; interactivity